2019
DOI: 10.1002/ffj.3526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of roselle (Hibiscus sabdariffa L.) extracts on the rheological, textural, and antioxidant activity of fermented milks

Abstract: The study aims to evaluate the rheological, textural, and antioxidant activity of fermented milks with the addition of roselle (Hibiscus sabdariffa L.) extracts at concentrations of 0.0, 0.1, 0.2, and 0.3% (CFM, RFM1, RFM2, and RFM3). The chemical composition of the fermented milks, including crude protein, fat, ash, total solids and non‐fat solids, were also determined. Gas chromatography–mass spectroscopy (GC‐MS) detected 42, 46, 47, and 49 kinds of volatile flavour compounds in CFM, RFM1, RFM2, and RFM3, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…These flowers are characterized by a high content of bioactive compounds such as polyphenolic acid, flavonoids, and anthocyanins, which exhibit strong antioxidant properties. They are known to stimulate the immune system and increase the production of cytokines, thereby reducing the risk of various cardiovascular diseases, obesity-related conditions, diabetes, and carcinogenic activity in addition to acting as immunomodulators [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These flowers are characterized by a high content of bioactive compounds such as polyphenolic acid, flavonoids, and anthocyanins, which exhibit strong antioxidant properties. They are known to stimulate the immune system and increase the production of cytokines, thereby reducing the risk of various cardiovascular diseases, obesity-related conditions, diabetes, and carcinogenic activity in addition to acting as immunomodulators [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, anthocyanin is unstable in the presence of oxygen, enzymes, copigments, metal ions, sulfur dioxide, sugar, sugar degradation products, as well as variations in temperature, pH, light, and solute concentration (Ochoa‐Velasco et al, 2017; Wallace, 2010). Studies have shown that the hibiscus extract has a high level of antioxidant activity and such effect may be related to the presence of anthocyanins (Da‐Costa‐Rocha et al, 2014; Maciel et al, 2018; Su et al, 2020).…”
Section: Introductionmentioning
confidence: 99%